Biological reduction of nitroimidazole-functionalized gold nanorods for photoacoustic imaging of tumor hypoxia. Issue 29 (29th May 2019) - Umehara, Yui; Kageyama, Toki; Son, Aoi; Kimura, Yu; Kondo, Teruyuki; Tanabe, Kazuhito
Abstract : Tumor-selective accumulation of gold nanorods (GNR) has been demonstrated for visualization of tumor hypoxia by photoacoustic imaging. Abstract : Tumor-selective accumulation of gold nanorods (GNR) has been demonstrated for visualization of tumor hypoxia by photoacoustic imaging. We prepared GNRs with hypoxia-targeting nitroimidazole units (G-NI) on their surface. Biological experiments revealed that G-NI produced a strong photoacoustic signal in hypoxic tumor cells and tissues.